If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -5) = 27 Reorder the terms: 3(-5 + 2x) = 27 (-5 * 3 + 2x * 3) = 27 (-15 + 6x) = 27 Solving -15 + 6x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 6x = 27 + 15 Combine like terms: -15 + 15 = 0 0 + 6x = 27 + 15 6x = 27 + 15 Combine like terms: 27 + 15 = 42 6x = 42 Divide each side by '6'. x = 7 Simplifying x = 7
| x+(x+6)+12=66 | | 71-2x=34x+23 | | 14m+6n-4m+7n= | | (x+6)+12=66 | | 14-7x=110-35x | | 6a+1=2a+25 | | X^2-71*x+72=0 | | 2x+3=19+x | | -26-7x=110-35x | | -3x^2=-12 | | 180-7x=20x+21 | | 9t-3=8t-18 | | 7y+3=12y+8 | | -155-7x=10x+15 | | -155-7x=10x+25 | | 18+4y=18 | | 8x^2+3x+10=0 | | 6n-7=3n+2 | | 5x-18=22 | | 3x+7x=8 | | 3n+6=n+10 | | 7x^2-6x-111=0 | | 4.4x+3.8=13.2 | | 4x+34=12x-38 | | 4*0.5-3y=11 | | 2x+9=51-8x | | 10x-29=71 | | 76-4x=7+21 | | 4x-3*-3=7 | | 3x+13=39-5x | | 17x-17+31+9x-69-18x=-39 | | 4x+-3=-1 |